Answer:
[tex]f(x)=(x-3)(x^2-8x+17)[/tex]
Or:
[tex]f(x)=x^3-11x^2+41x-51[/tex]
Step-by-step explanation:
To find our factors, we can work backwards.
We know that 3 is a zero. This means that:
[tex]x=3[/tex]
Subtract 3 from both sides:
[tex](x-3)=0[/tex]
So, (x-3) is one of our factors.
We also know that (4+i) is a zero. So:
[tex]x=4+i[/tex]
First, let’s isolate the imaginary. So, subtract 4 from both sides:
[tex](x-4)=i[/tex]
Now, let’s square both sides:
[tex](x-4)^2=(i)^2[/tex]
Expand the left. Evaluate the right:
[tex](x^2-8x+16)=-1[/tex]
Add 1 to both sides. So, our factor is:
[tex](x^2-8x+17)=0[/tex]
Hence, our polynomial function is:
[tex]f(x)=(x-3)(x^2-8x+17)[/tex]
This is also the least degree since we did the most minimum we can do to solve backwards.
Further Notes:
If we want to convert this to standard form, we can distribute:
[tex]f(x)=(x^3-8x^2+17x)+(-3x^2+24x-51)[/tex]
Combining like terms will yield:
[tex]f(x)=x^3-11x^2+41x-51[/tex]